1992
DOI: 10.1111/j.1432-1033.1992.tb16566.x
|View full text |Cite
|
Sign up to set email alerts
|

An oxidized analog of α‐human atrial natriuretic polypeptide is a selective agonist for the atrial‐natriuretic‐polypeptide clearance receptor which lacks a guanylate cyclase

Abstract: The differences in biological functions between a-human atrial natriuretic polypeptide (a-hANP) and its oxidized analog, MetSO-a-hANP, have been investigated. Analysis of the ANP receptor subtypes by affinity labeling has shown that a bovine pulmonary aortic endothelial cell line (CPAE cells) primarily expresses ANP-R1 (R, receptor) coupled to particulate guanylate cyclase, while Hela cells from human cervical carcinoma predominantly express ANP-R2, which lacks a guanylate cyclase. a-hANP could bind to both AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…Testing of synthetic peptide analogs on position 188 mutant receptors confirmed the role of this site in determining the binding properties of rat or human NPR-C. However, in testing synthetic peptides such as hANP(F8Y) [12], hANP(G10K,RI1S) [13], hANP(O-Met) [14] and cANF [15] on the full set of mutant receptors we have now identified a second mutant, rY205N, with an altered pharmacology which is in between the high affinity state of rat C-IgG and the lower affinity state of human C-IgG (Fig. 1).…”
Section: Identification Of the Binding-modulating Residue 205mentioning
confidence: 99%
“…Testing of synthetic peptide analogs on position 188 mutant receptors confirmed the role of this site in determining the binding properties of rat or human NPR-C. However, in testing synthetic peptides such as hANP(F8Y) [12], hANP(G10K,RI1S) [13], hANP(O-Met) [14] and cANF [15] on the full set of mutant receptors we have now identified a second mutant, rY205N, with an altered pharmacology which is in between the high affinity state of rat C-IgG and the lower affinity state of human C-IgG (Fig. 1).…”
Section: Identification Of the Binding-modulating Residue 205mentioning
confidence: 99%
“…8). In fact, NPRC has been shown to bind fragments of the natriuretic peptide, and some of these peptides lack the elements that can form pseudo two-fold symmetry in the peptides 31,32 . To bind to peptides lacking pseudo two-fold symmetry and to transmit its binding signal into the cell, the NPRC might require a signal transmission mechanism that does not depend on ligands having a pseudo two-fold symmetry.…”
Section: Discussionmentioning
confidence: 99%
“…12 -hANP comprises a methionine sulfoxide molecule formed through sulfur oxidation in Met12 of hANP , which inhibits its ANP receptor agonistic properties 30,31 . The crystal structure complexed with hANP (Fig.…”
Section: Met(o)mentioning
confidence: 99%
“…When the NPR-C selective analog cANF [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] was coinfused with ANP in the isolated, perfused, rat kidney, these investigators observed a trend toward both increased potency (ED 50 ) and an increased maximal response for urinary sodium excretion (13). An analogous experiment has been described in vivo for coinfusion into rats of hANP and the analog hANP(0-Met) with an oxidized methionine at position 12 (33). This analog is more selective for NPR-C than NPR-A (19,22,33), and when coinfused with hANP there is a synergistic effect on diuresis (natriuresis was not measured) (33).…”
Section: Discussionmentioning
confidence: 99%
“…An analogous experiment has been described in vivo for coinfusion into rats of hANP and the analog hANP(0-Met) with an oxidized methionine at position 12 (33). This analog is more selective for NPR-C than NPR-A (19,22,33), and when coinfused with hANP there is a synergistic effect on diuresis (natriuresis was not measured) (33). For both of these experiments (13, 33) the selective blocking, or binding, of NPR-C by these ANP analogs resulted in an increased renal response during coinfusion with ANP, consistent with our proposed role for NPR-C as a decoy receptor attenuating renal NPR-A activation.…”
Section: Discussionmentioning
confidence: 99%